2016
DOI: 10.1536/ihj.16-112
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness Is Significantly Associated With Left Ventricular Diastolic Dysfunction in Patients With Cardiovascular Disease

Abstract: SummaryLeft ventricular (LV) diastolic dysfunction is considered the main cause of heart failure with preserved ejection fraction (HFpEF). There have been few reports on the correlation between LV diastolic dysfunction and arterial stiffness in patients with clinical cardiovascular disease.This cross-sectional study enrolled 100 patients (67 men, 33 women; mean age, 70 years). All participants were diagnosed with cardiovascular disease. A total of 89 (89%) patients had coronary artery disease or HF. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 41 publications
3
22
1
5
Order By: Relevance
“…Decrease of HDLC levels is mainly related to inadequate dialysis and malnutrition. It has been reported that 50-70% of hemodialysis patients had increased plasma Lp(a) levels, higher than 0.3 g/L, inconsistent with the results of this article [8, 23], perhaps due to different conditions, different ways, different time to start doing hemodialysis and treatment course, and all the above factors can affect the metabolism of Lp(a) [22]; Lp(a) level was increased significantly in diabetic patients; however, it was found irrelevant to diabetes in this study. In addition, variability of Lp(a) levels is huge dependent on the size of samples.…”
Section: Discussioncontrasting
confidence: 89%
“…Decrease of HDLC levels is mainly related to inadequate dialysis and malnutrition. It has been reported that 50-70% of hemodialysis patients had increased plasma Lp(a) levels, higher than 0.3 g/L, inconsistent with the results of this article [8, 23], perhaps due to different conditions, different ways, different time to start doing hemodialysis and treatment course, and all the above factors can affect the metabolism of Lp(a) [22]; Lp(a) level was increased significantly in diabetic patients; however, it was found irrelevant to diabetes in this study. In addition, variability of Lp(a) levels is huge dependent on the size of samples.…”
Section: Discussioncontrasting
confidence: 89%
“…E, A, E/ A, and E/e' are known as other Doppler indices for evaluating left ventricular diastolic function. 5,6) However, E, A, and E/A need careful interpretation, since these show a 'pseudonormal or restrictive filling pattern' in advanced diastolic dysfunction. E and A are combined in one component in increased heart rate, which is likely to occur in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Также в когорте больных сердечно-сосудистыми заболеваниями было показано, что при патологическом СЛСИ отношение E/e' было выше, чем при нормальном СЛСИ (15,5±6,4 против 12,5±2,9; р = 0,003). У больных ХСН с сохраненной фракцией выброса левого желудочка отмечены подобные значения данного отношения в группах больных с различным СЛСИ (17,2±5,9 против 13,0±3,1; р = 0,026) [18]. У больных ОНМК ранее структурные показатели ЛЖ не исследовали, в настоящем исследовании таких закономерностей не выявлено.…”
Section: Discussionunclassified